Household Savings and Marriage Payments: Evidence from Dowry in India - S Anukriti; Sungoh Kwon; Nishith Prakash (Institute of Labor Economics (IZA), 2018)
This paper examines how traditional marriage market institutions affect households' financial decisions. We study how bride-to-groom marriage payments, i.e., dowries, influence saving behavior in rural India. Exploiting variation in firstborn gender and heterogeneity in dowry amounts across marriage markets, we find that the prospect of paying higher dowry increases household savings, which are primarily financed through increased paternal labor supply. This is the first paper that highlights this alternative motive for savings in dowry-paying societies. However, we find no impacts of dowry expectations on son-preferring fertility behaviors and investments in girls.
Keywords: J1; D14; O15; 330; household savings; dowry; marriage payments; India; labor supply; fertility; sex ratio; child investments